Implementasi Manajemen Strategik Unit Produksi SMKN 3 Mataram - Irawan, M Ary (Jurnal Paedagogy, 2018)
In order to improve the quality of education, especially in SMK, so that it can be achieved as expected, it should be supported by effective strategic management. One of the priorities that must be considered is the production unit and school services as a source of learning for students. The activities of production and service units in schools can be used as a source of learning through the planning process, production activities to marketing products in the form of goods or services. Through the activities of production and service units in schools, students are in a learning situation that is closer to the real conditions with the business or industrial world. For this reason, this study focuses more on studying the "Implementation of Strategic Management at the Production Unit of SMKN 3 Mataram". The instrument used in this study is the researcher himself, where the researcher will make observations, documentation, and interviews, while the qualitative data analysis method is through three activities, namely (1) data reduction, (2) data presentation (data display). , and (3) drawing conclusions and verification (conclusion drawing / verification). Based on the research focus, the results of this study are formulated in 3 conclusions, namely (1) Strategic planning for the production unit of SMKN 3 Mataram, including: (a) Conformity between Production Unit Program Objectives and School Vision and Mission, and (b) Developing Production Unit Work Programs Periodically; (2) The strategic implementation of the SMKN 3 Mataram production unit includes: (1) Collaborating with government and private agencies, (2) Marketing or marketing of production units is carried out by school members, namely school principals, teachers, students, parents / guardians of students. and alumni, (3) Empowerment of alumni and students as workforce, (4) Implementation of production activity time does not interfere with PBM, and, (5) Transparency in financial management; and (3) Strategic supervision of the production unit of SMKN 3 Mataram includes: (1) Distribution of customer satisfaction instruments, (2) Supervision in the form of activity reports that are compiled periodically, namely reports per semester, and annually.